The economic tortuous liability in English law. A comparative study with the illegal competition in the Iraqi law - علي يونس صلاح الدين (Journal of Legal Sciences, 2019)
The economic tortious liability in the English law is based upon economic Torts are considered as a type of the ancient and deep-rooted torts, aiming at breaching the rules of legal and equitable trade competition. and which are included in the customary English law of torts, based upon the judicial precedents decided by English courts. It is worth-bearing in mind that the economic torts are classified into two main types. That is to say, the general economic torts and the misrepresentation economic torts. Whereas the Iraqi legislator left the regulation of the illegal competition to the general rules of the delictual liability in the Iraqi civil law No. (40) of 1951.